2011
DOI: 10.1017/s003382220003914x
|View full text |Cite
|
Sign up to set email alerts
|

Are the Fractionation Corrections Correct: Are the Isotopic Shifts for 14C/12C Ratios in Physical Processes and Chemical Reactions Really Twice Those for 13C/12C?

Abstract: ABSTRACT. Conventional radiocarbon calculations correct for isotopic fractionation using an assumed value of 2.0 for the fractionation of 14 C relative to 13 C. In other words, isotopic discrimination in physical and chemical processes is assumed to cause relative shifts in 14 C/ 12 C ratios that are exactly double those of 13 C/ 12 C. This paper analyzes a 1984 experiment that produced a value for the fractionation ratio in photosynthesis of 2.3, which is used to this day by some researchers in the fields of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Several speleothem geochemical modeling studies have used a value of 2.3 for fractionation changes in 14 C/ 12 C vs. 13 C/ 12 C based on an attempt to determine the fractionation of 14 C relative to 13 C in photosynthesis (Saliege and Fontes, 1984). The experiment was probably compromised by contributions of fossil fuel and the value of 2.3 has no support from quantum theory (Southon, 2011).…”
Section: Soil Carbon Modelmentioning
confidence: 99%
“…Several speleothem geochemical modeling studies have used a value of 2.3 for fractionation changes in 14 C/ 12 C vs. 13 C/ 12 C based on an attempt to determine the fractionation of 14 C relative to 13 C in photosynthesis (Saliege and Fontes, 1984). The experiment was probably compromised by contributions of fossil fuel and the value of 2.3 has no support from quantum theory (Southon, 2011).…”
Section: Soil Carbon Modelmentioning
confidence: 99%
“…The quotient of diffusion coefficients for a rare and common isotope is also the inverse of the fractionation factor, α, which is 1.0044 for 13 CO 2 diffusion through soil (Cerling et al, 1991), and is estimated to be approximately 1.0088 for 14 CO 2 (Southon, 2011). Using this relationship, we can simplify and discretize Eq.…”
Section: Surface Flux 14 Comentioning
confidence: 99%
“…FM was related to the sample 14 C / 12 C ratio following the derivation in Southon et al (2011), where it is shown that 14 C activity ≈ 14 C / 12 C. In the equation above [ 14 C / 12 C] S is the sample 14 C ratio, δ 13 C is the sample 13 C abundance in ‰ notation, which is used to normalize the 14 C ratio for mass-based fractionation to δ 13 C = −25 ‰, and 0.95 · [ 14 C / 12 C] OX1 is the normalized 14 C ratio of the oxalic acid I standard.…”
Section: Surface Flux 14 Comentioning
confidence: 99%
“…Deviations in this value add only a small amount of error to resulting probable ages derived from 14 C dating (Wigley and Muller 1981). While Wigley and Muller (1981) concluded that variation in b from 2.0 would not significantly impact 14 C dates, Southon (2011) has recently suggested that the combination of anomalies in the literature and increasing accuracy and precision in 14 C dating necessitate a reappraisal of the assumed value of 2.0 (Southon 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Given recent discussion regarding the fractionation ratio (Southon 2011) it may be worthwhile to investigate natural fractionation effects in isolation. The present article uses common models of carbon isotope fractionation used in plant biochemistry to model natural variation in carbon isotope fractionation during photosynthesis.…”
Section: Introductionmentioning
confidence: 99%